Serum oxidative stress parameters of women with hypothyroidism - Coria, M. J.; Pastrán, A. I.; Gimenez, M. S. (Acta Biomedica Atenei Parmensis, 2009)
In order to study the effects of hypothyroidism on parameters of oxidative stress in woman, we determined the values of thiobarbituric acid reactive substances (TBARS), Nitric Oxide (NO) and Paraoxonase (PON-1) using phenylacetate as substrates in serum. Women in fertile age were separated into three groups: a- euthyroidism (ET) control group, b- overt hypothyroidism (OHT) and c- subclinical hypothyroidism (SHT). TBARS concentration and the PON-1 activity as aryl esterase activity did not show differences between OHT, SHT and ET woman. The concentration of NO increased in OHT compared to ET. The SHT and ET NO values were not significantly different, but the NO level was higher in the serum of OHT compared to SHT. The OHT selectively increased the NO levels but did not modify the parameters of oxidative stress in the serum of fertile-age women.